Introduction to community and public health - Sharma, Manoj; Branscum, Paul (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
'One of the needs of all students in public health, health education, and related disciplines is to understand the basics of community and public health. Currently, there are very few books on this topic, and none of the existing textbooks covers all the essential areas. This book is designed to primarily prepare students in public health and health education with the basics in all five of the core areas of community and public health identified by the Association of Schools of Public Health and Council on Education for Public Health (CEPH): biostatistics, environmental health sciences, epidemiology, health policy and management, and social and behavioral sciences. Our purpose has been to provide a text in the area of community and public health for undergraduate students (B.S., B.A.), graduate students (M.S., M.A., MPH), and both entry level and advanced level practitioners in public health, health education, and health promotion'--
Revised edition of: Introduction to community and public health / by Manoj Sharma, Paul Branscum, and Ashutosh Atri. [2014].
Includes bibliographical references and index.
Keywords: Community Health Planning; Public Health; Health Education; Health Promotion; Biostatistics